Pembuatan Standard Operating Procedure (SOP) Arsip Dinamis Aktif di Unit Procurement & Logistic Staff, Proyek Indarung VI PT Semen Padang - Rikasari, Fauzia; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper discusses about the Making of Standard Operating Procedure (SOP) of Active Dynamic Archive at Unit Procurement & Logistic Staff, Indarung VI Project PT Semen Padang. This study aims to; (1) to describe the making of active dynamic operating system standard (SOP) in the Procurement & Logistic Staff unit, Indarung VI Project of PT Semen Padang; (2) to know the result of standard operating procedure (SOP) of active dynamic archive in Unit Procurement & Logistic Staff, Indarung VI Project PT Semen Padang. The method used is descriptive method. Data were collected through observation and direct interview with archival officer at Procurement & Logistic Staff unit, Indarung VI Project PT Semen Padang. Based on research result; In the management of active dynamic archives using SOPs to direct and improve the quality of work processes in active dynamic records management in the Procurement & Logistic Staff unit, Indarung VI Project of PT Semen Padang can be concluded from the process of archive creation, archival recording and archive maintenance and use.Keyword: Standard Operating Procedure (SOP), Active Dinamic Archive